A Business Model for Private Higher Education in a Digitalized Era - Senny Luckyardi; Yogi Suprayogi; Eddy Soeryanto Soegoto; Gordana Pesakovic (Australasian Accounting, Business and Finance Journal, 2024)
The higher education sector is embroiled in a continuous digital transformation process, resulting in a significant need for an innovative business model need for an innovative business model. Private universities are required to survive amidst competition in this digital era. The need for an innovative business model is reinforced by the fact that Student Satisfaction (SS) still needs to improve at Private Universities in West Java, Indonesia. This research develops a Smart University Image (SUI) as a novelty in a new business model to increase SS. In addition, SUI was developed because brand image theory was deemed insufficient and inconsistent from a semantic or functional standpoint when applied to a smart university (SU). The SUI dimensions developed are Cognitive, Conative, Emotive, and Collaborative. This research also aims to develop and test the SUI model synthesized from Relationship Marketing. A quantitative method is used in this research using proportional purposive sampling data collection techniques. The questionnaire distribution was based on the criteria of respondents who were second and third-year students at private universities (PU) in West Java, Indonesia, and were classified as SU. The data analysis used Structural Equation Modeling (SEM), partial model test, and Sobel test to determine the strength of the mediation role in this research model. The findings of this research state that the SUI relationship significantly affected SS, which means it is appropriate to be applied to new business models in the higher education sector. The recommendations from this research findings are that private universities need to develop business models that apply high technology to create student engagement and SS in the framework of a smart university.
Keywords: Private Higher Education; Smart University Image; Student Satisfaction